(untitled) (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
Although the application of IoT technologies in water management and agriculture offers numerous advantages, several challenges arise during their implementation. First of all, environmental conditions such as extreme temperature variations, high humidity, and dust negatively affect the operational lifetime of sensors and devices. Therefore, it is essential to develop hardware solutions with weather-resistant and robust enclosures. In addition, the lack of stable internet coverage in remote areas makes real-time data transmission difficult, which necessitates the expansion of network capabilities. Power management is also a critical issue, as sensors are often powered by batteries or solar energy. To ensure their long-term operation, efficient energy management strategies and energy harvesting technologies are required.